Haemophilia, human immunodeficiency virus and human immunodeficiency virus pathogenesis - Lederman, Michael M. (Thrombosis and Haemostasis, 2010)
In July 1982, the occurrence of three cases of acquired immunodeficiency syndrome (AIDS) in men with haemophilia was an immediate signal to Oscar Ratnoff that AIDS was transmissible through blood products. Work that he led provided important and clear indication that the AIDS agent was transmissible through pooled plasma products and had rapidly infected many men who had haemophilia. Before the blood supply was protected, the risk for infection in haemophilia was related directly to the intensity of therapy with pooled anti-haemophilic factor concentrates. Studies performed among the small proportion of haemophiliacs who remained uninfected despite heavy exposure to these plasma products revealed that the rare protective genotype – homozygosity for the 32 base pair deletion in the CCR5 gene was heavily concentrated in this population. Among those who did not have this protective genotype, a state of diminished immune activation distinguished these high risk uninfected haemophiliacs from haemophiliacs who later acquired human immunodeficiency virus (HIV) infection and from healthy uninfected controls. Immune activation state may not only predict risk for HIV acquisition but also appears to be an important predictor and likely determinant of HIV disease progression. The potential drivers of immune activation in chronic HIV infection include HIV itself, other co-infecting pathogens, homeostatic responses to cytopenia as well as the recently recognised phenomenon of translocation of microbial products across a damaged gut mucosal surface. This latter process is particularly compelling as clinical studies have shown a good relationship between indices of microbial translocation and markers of both immune activation and T cell homeostasis in chronic HIV infection. More recently, we have also found evidence that these microbial products also may drive a heightened tendency to thrombus formation in HIV infection via induction of monocyte tissue factor expression. Thus systemic exposure to microbial elements that are translocated through a gut mucosa damaged in the first few weeks of HIV infection may contribute to the pathogenesis of both immune deficiency and the heightened risk for vascular events that have been noted in persons with HIV infection.
Keywords: Infectious diseases; immunity; viral infection